Single-Cell Analysis of Circulating Tumor Cells as a Window into Tumor Heterogeneity - Miyamoto, David T. (Cold Spring Harb Symp Quant Biol, 2017)
Recent advances in microfluidic approaches have enabled the efficient isolation and detailed molecular characterization of circulating tumor cells (CTCs) in the peripheral blood of patients with cancer. Single-cell molecular analyses of CTCs reveal a tremendous degree of intracellular heterogeneity in CTC populations, reflective of heterogeneity across different patients as well as the underlying heterogeneity of tumors within each individual patient. These studies have enabled the identification of heterogeneous drug resistance mechanisms that can coexist in treatment refractory tumors. CTC analyses also enable serial noninvasive monitoring in patients and can capture the emergence of tumor heterogeneity over time, whether due to tumor evolution through genetic instability or through cellular plasticity. The presence and extent of intratumoral heterogeneity as revealed through the study of CTCs have important clinical implications for understanding and predicting the development of treatment resistance in a variety of solid tumors and for formulating appropriate therapeutic strategies in the effective treatment of cancer.